PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PADA KSP. CITRA LESTARI - Ngakan Putu Surya Harta Bhuwana; I Nengah Arsana; Surahman Hidayat (PT Seval Literindo Kreasi, 2022)
This study aims to examine the effect of Reward and Punishment on employee work performance. So that this research variable consists of 2 (two) independent variables, namely Reward (X1), Punishment (X2), and the dependent variable is employee performance (Y). The population of this research is KSP. Citra Lestari is involved in the company. The type of research used in this research is associative research. Samples were taken using non-probability sampling with saturated samples where all employees were sampled, amounting to 30 people. The data was obtained by distributing 30 questionnaires to the respondents in the KSP. Citra Lestari. Data were analyzed using multiple linear regression. The results show that Reward and Punishment have a significant effect on work performance as evidenced by t-test analysis. Each x variable has t count > t table, namely Reward (4.915 > 2.051) and Punishment (1997 < 2.051). The results of this study also show that Reward (X1), Punishment (X2) simultaneously have a significant effect on employee performance (Y) with a calculated F value > F table (0.000 < 0.05) and Adjusted R Square of 0.761. And the Reward variable is the variable that most dominantly influences employee performance (Y), which is indicated by the highest beta coefficient value, which is 0.531 or 53.1%.